Importance of tax administration of multinational companies in developed countries. (Foreign experience) (Eurasian Research Bulletin, 2024)
In this article, suggestions and recommendations are formed through the economic analysis of tax evasion by multinational companies and the role of taxes, the role of taxes in attracting foreign investors to our country